Applications of Optical Fibers for Sensing 2019
DOI: 10.5772/intechopen.83622
|View full text |Cite
|
Sign up to set email alerts
|

Distributed, Advanced Fiber Optic Sensors

Abstract: India is poised to use nuclear energy in a big way. The safety of these systems depends upon monitoring various parameters in hazardous environment like high radiation, high temperature exceeding 1000°C, and gas/coolant leakages. In this chapter, we shall dwell on basics of distributed sensing, related instrumentation, device fabrication, and actual advanced field applications. Techniques like Raman scattering, resonance response of fiber gratings, and selective absorption are employed for design, development,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Distributed type of sensing is one where spatial distribution of measurand is measured by time-domain reflectometry. 22 Rayleigh scattering, Raman scattering, and Brillouin scattering work as distributed-based optical sensors, but they are seldom used due to high cost. In the case of point-based sensors, sensing mechanism is performed at a discrete point of the fiber.…”
Section: Optical Engineeringmentioning
confidence: 99%
“…Distributed type of sensing is one where spatial distribution of measurand is measured by time-domain reflectometry. 22 Rayleigh scattering, Raman scattering, and Brillouin scattering work as distributed-based optical sensors, but they are seldom used due to high cost. In the case of point-based sensors, sensing mechanism is performed at a discrete point of the fiber.…”
Section: Optical Engineeringmentioning
confidence: 99%
“…Kher et al [69,70] also reported about an LPG written in an endlessly single mode (ESM) photonic crystal fiber (PCF) ESM-12-02 made by Crystal Fiber, Denmark. The grating was fabricated using a CO 2 laser based setup, with a period of 450 µm and presented high strain sensitivity and negligible temperature response in comparison to LPGs in the standard fiber [71].…”
Section: Gamma Irradiation Of Co 2 -Written Lpgsmentioning
confidence: 99%
“…NASA also reported similar works on fiber sensing technologies, in particular a multi-point fiber optic hydrogen micro-sensor system for leak detection for launch vehicles. The system contains chemically reactive coatings whose reflection behaviour changes in proportion to the hydrogen concentration and are used as leak detectors [120].…”
Section: Fiber Optic Sensingmentioning
confidence: 99%